Food systems for improved human nutrition: linking agriculture, nutrition, and productivity - Kataki, Palit K.; Babu, Suresh Chandra (2002)
This item was also published as a book, available at https://www.routledge.com/Food-Systems-for-Improved-Human-Nutrition-Linking-Agriculture-Nutrition-and-Productivity/Kataki-Babu/p/book/9781560221036